Folk pedagogu — the basis of patriotism - Abildina, S.K.; Musina, V.T. (KSU Publ., 2017)
Authors describe the problems of patriotic education, decide on problems arising up in an educator process in general schools. Quote labours of scientists investigating patriotic education, examine influence of folk pedagogics on the problem of patriotic education. In the article next concepts are exposed: "modern Kazakh society", "patriot of people", "national patriotism", "folk pedagogics", "Kazakhstan patriotism", their intercommunication is shown in a pedagogical theory and practice. The national values of the Kazakh people are examined: traditions, customs, faith, verbal and writing literature, folk music, that find a reflection in globalization of educator process.Authors open the main directions of a national educational system at Kazakhs and its tradition. So, one of the most important traditions of family education at Kazakhs is the knowledge of the family tree, the family tree. Features of family education which in the Kazakh national pedagogics is considered as the prime public necessity reveal. The author of the paper describes the use of traditional methods of national pedagogics in moral education of children in the conditions of modern society. The essence, techniques and methods of Russian national pedagogics used in moral education of children are revealed.
Ұлттық педагогика-патриотизм негізі
Народная педагогика-основа патриотизма
Keywords: people; society; patriotic education; patriotism; patriotic consciousness; national education; Kazakhstani patriotism; globalization; national values; people's education system; customs; faith; traditions